PIEZO1 Hypomorphic Variants in Congenital Lymphatic Dysplasia Cause Shape and Hydration Alterations of Red Blood Cells - Andolfo, Immacolata; De Rosa, Gianluca; Errichiello, Edoardo; Manna, Francesco; Rosato, Barbara Eleni; Gambale, Antonella; Vetro, Annalisa; Calcaterra, Valeria; Pelizzo, Gloria; De Franceschi, Lucia; Zuffardi, Orsetta; Russo, Roberta; et al. (Frontiers in Physiology, 2019)
PIEZO1 is a cation channel activated by mechanical force. It plays an important physiological role in several biological processes such as cardiovascular, renal, endothelial and hematopoietic systems. Two different diseases are associated with alteration in the DNA sequence of PIEZO1: (i) dehydrated hereditary stomatocytosis (DHS1, #194380), an autosomal dominant hemolytic anemia caused by gain-of-function mutations; (ii) lymphatic dysplasia with non-immune fetal hydrops (LMPH3, #616843), an autosomal recessive condition caused by biallelic loss-of-function mutations. We analyzed a 14-year-old boy affected by severe lymphatic dysplasia already present prenatally, with peripheral edema, hydrocele, and chylothoraces. By whole exome sequencing, we identified compound heterozygosity for PIEZO1, with one splicing and one deletion mutation, the latter causing the formation of a premature stop codon that leads to mRNA decay. The functional analysis of the erythrocytes of the patient highlighted altered hydration with the intracellular loss of the potassium content and structural abnormalities with anisopoikolocytosis and presence of both spherocytes and stomatocytes. This novel erythrocyte trait, sharing features with both hereditary spherocytosis and overhydrated hereditary stomatocytosis, complements the clinical features associated with loss-of-function mutations of PIEZO1 in the context of the generalized lymphatic dysplasia of LMPH3 type.